The Influence of Bath Temperature on the Properties of SILAR Deposited Cobalt Selenide Thin Films - Ho, S. M.; Anand, T. J. S. (Engineering, Technology & Applied Science Research, 2021)
In this paper, cobalt selenide thin films have been deposited onto glass slides with the SILAR method under various bath temperatures. The structure, optical properties, and morphology of thin films were investigated. The X-ray diffraction patterns confirmed that the number of peak intensities increased with increasing bath temperature. From the AFM images, bigger sizes and thicker films were observed for the films prepared at 80°C. The average grain size was estimated to be 0.2µm, 0.15µm, and 0.25µm when the bath temperature was 40°C, 50°C, and 80°C respectively. The highest absorbance value was observed for films prepared at 80°C. The band gap values range from 2eV to 2.4eV.